Human Capital Risk Factors on Workforce Sustainability Performance: an Organizational Behavior Perspective - Taufiq Rahmat (Program Studi Manajemen, Universitas Al Ghifari, 2025)
This study aimed to analyze the impact of job insecurity and job stress as human capital risks on workforce sustainability performance. It is a descriptive study with a quantitative approach. Data were collected from industrial workers in Indonesia using a structured questionnaire. Structural Equation Modeling with the PLS technique was applied for analysis. The results showed that job insecurity had a stronger effect on turnover intention compared to job stress. The model explained 64.4% of the variance in turnover intention. The findings highlight the need for integrated human resource strategies to mitigate psychological threats that reduce workforce sustainability.